One day in the life of Ivan Denisovich - Courtenay, Tom; Burke, Alfred; Maxwell, James; Solzhenit︠s︡yn, Aleksandr Isaevich, 1918-2008 (Sony Video Software, 1988)
The story of a prisoner's fight to retain sanity and self worth in a Stalinist work camp.